The Effectiveness of Biodiversity on Mount Ungaran Central Java e-Encyclopedia as Learning Resources in The Pandemic Era - Dwi Setyorini; Margareta Rahayuningsih; Ning Setiati (Pendidikan Kimia Unimus, 2022)
This study aims to determine the effectiveness of the Biodiversity on Mount Ungaran electronic encyclopedia in learning Biology in the Covid-19 Pandemic Era. The research design used was one group pretest-posttest design. The instrument used was about thinking skills. The sample in this study was 34 public school students in Central Java. The instrument used was a test of learning outcomes with 35 questions. Data were analyzed using the N-Gain test and Paired Sample t-test. The percentage analysis was used to see students’ responses to the e-encyclopedia used during the learning process. Google classroom and google meet were used in the learning process. The data analysis showed that the N-Gain result was 0.625 with a classical completeness value of 94.11%. The t-test results showed a significant difference in the pretest and post-test data with a significant value of <0.05. In addition, the response of students tested on a small scale obtained 76.90% in the high category. Therefore, the effectiveness of the electronic encyclopedia of biodiversity on Mount Ungaran was moderate.